(untitled) (Journal of Cancer Research Updates, 2025)
Background: Breast cancer remains one of the most prevalent tumors among females worldwide, and current prognostic methods are limited in their ability to accurately predict tumor aggressiveness and long-term outcomes. KI67 is a nuclear protein marking active cell proliferation and is associated with tumor differentiation, growth, and breast cancer subtypes. Objective: This study aims to assess KI67 in benign and malignant breast tissues and explore its potential association with clinical outcomes. Methodology: Immunohistochemistry was used to assess KI67 staining in benign (n=57) and malignant (n=430) breast tissue samples. KI67 expression was then correlated with clinic opathological data, such as grade and stage, and breast cancer molecular subtypes. Results: Increased KI67 was significantly found in breast carcinoma compared to benign tissues (P <0.0001). A positive association was observed between KI67 immunostaining and tumor grade (P <0.0001), tumor size (P0.007), and molecular subtype (P 0.002).No significant relationship was recognized between KI67 immunostaining and lymph node involvement. Conclusion: KI67 might be involved in the aggressiveness of malignancy. Further research is needed to determine the significance of KI67 inbreast carcinoma and its potential as a biomarker for breast cancer progression.